Analyses of energy use and greenhouse gas emissions (GHG) in watermelon production - Demir, Cihan (International Journal of Agricultural and Biological Engineering, 2023)
The aim of this research is to conduct an energy use efficiency and greenhouse gas (GHG) emission analysis in watermelon production that took place in Kırklareli Province of Turkey during the 2021 production season. This research contains calculations of Energy use efficiency, specific energy, energy productivity and net energy, energy input types, GHG emissions and GHG ratio. Survey, observation and data calculations are related to the 2021 production season. The data used in the research were collected from 30 different (accessible) farms through face-to-face surveys with full count method. EI and EO were calculated as 15698.99 MJ/hm2 and 104784.91 MJ/hm2, respectively. In relation to production inputs, 24.29% of the energy inputs consisted of chemical fertilizers energy (3813.34 MJ/hm2), 20.04% consisted of transportation energy (3146.19 MJ/hm2), 10.63% consisted of diesel fuel energy (1668.52 MJ/hm2), 7.44% consisted of human labour energy (1168.09 MJ/hm2), 6.50% consisted of plant energy (1021.02 MJ/hm2), 5.76% consisted of electricity energy (904.50 MJ/hm2), 5.18% consisted of machinery energy (813.44 MJ/hm2), 3.36% consisted of irrigation water energy (527.63 MJ/hm2), 2.85% consisted of organic fertilizer energy (446.72 MJ/hm2), 2.40% consisted of farmyard manure energy (376.62 MJ/hm2) and 0.67% consisted of chemicals energy (105.67 MJ/hm2). Energy use efficiency, specific energy, energy productivity and net energy were calculated as 6.67, 0.28 MJ/kg, 3.51 kg/MJ and 89085.91 MJ/hm2, respectively. The utilized total energy input in production was grouped as 27.19% direct energy, 72.81% indirect energy, 22.55% renewable energy and 77.45% non-renewable. Total GHG emissions and GHG ratio were determined as 492.82 kg CO2-eq/hm2, 0.01 kg CO2-eq/kg, respectively.Keywords: energy use, GHG analysis, GHG ratio, Turkey, watermelonDOI: 10.25165/j.ijabe.20231605.7918Citation: Demir C. Analyses of energy use and greenhouse gas emissions (GHG) in watermelon production. Int J Agric & Biol Eng, 2023; 16(5): 221-225.